Effect of Red Turi Leaf Extract (Sesbania grandiflora L.) on Hematological Values in Diabetic Male Mice - Dzannastia, Aulya; Kuswanti, Nur; Purnama, Erlix Rakhmad (LenteraBio : Berkala Ilmiah Biologi, 2023)
Diabetes mellitus can affect blood hematological values, such as hemoglobin levels and platelet counts. Red turi leaves contain compounds that have potential to treat diabetes and improve hematological values. The purpose of this study was to determine the effect of red turi leaves extract on hemoglobin levels and platelet counts in diabetic male mice, and to obtain the optimum dose. The research was conducted at Experimental Animal Laboratory of UNESA. Diabetic mice were made by 130 mg/kgBW alloxan induction. The study used RAL with six treatment groups i.e., negative control (KN), positive control (KP), glibenclamide group (KG), and extract (K1=250 mg/kgBW, K2=400 mg/kgBW, and K3=500 mg/kgBW ), each with four repetitions. Extract treatment was conducted for 14 days. Hemoglobin levels were measured using hemoglobin test strips and platelet counts using the Brecher Cronkite method. The data gained were analyzed using normality test, homogeneity test, One-Way Anova, Duncan test, and Tukey test. The results of analysis showed that red turi leaves extract had an effect on hemoglobin levels (p<0.05) and platelet counts (p<0.05). Based on the results was concluded that turi leaf extract had an effect on hemoglobin levels and platelet counts indiabetic mice with 400 mg/kgBW as the optimum dose.